EFFECT OF DIFFERENT NITROGEN DOSES ON PERFORMANCE OF BABY CORN (ZEA MAYS) UNDER LOCAL CONDITION IN KUSHMA, PARBAT, NEPAL - Kabita Bhat; Poojan Adhikari; Sushil Awasthi; Anu Panthy; Kiran Thapa; Saujan Acharya (Acta Scientifica Malaysia, 2024)
The study “Effect of Different Nitrogen Doses on Performance of Baby Corn under Local Conditions in Kushma, Parbat, Nepal” was conducted from February 2023 to July 2023 at Mudikuwa, Phalewas-04, Parbat district. Employing a Single Factorial Randomized Complete Block Design, the experiment included eight nitrogen treatments (0, 75, 115, 150, 190, 225, 260, and 300 kg/ha) with three replications. The field was divided into 24 plots, each measuring 2 meters by 2 meters, with a plant spacing of 40 cm by 20 cm. Standard baby corn cultivation practices were followed under open field conditions. Data on growth and yield parameters were collected, showing that the highest plant height, leaf number, and leaf length were recorded at 300 kg/ha, while the lowest were observed at 0 kg/ha (control). The longest cobs were found at 260 kg/ha, and the shortest at 0 kg/ha, although cob length differences among treatments were not statistically significant. The largest cob diameter was observed at 190 kg/ha, and the smallest at 0 kg/ha. The maximum number of cobs was recorded at 300 kg/ha, statistically similar to the 150, 190, and 225 kg/ha treatments. The optimum nitrogen dose for maximum cob weight was 150 kg/ha, with no significant yield increase beyond this dose. The highest harvest index was recorded at 190 kg/ha, statistically similar to the 150 kg/ha and higher doses. Overall, baby corn performed well with 150 kg/ha of nitrogen, proving to be economically viable.